THE MEANING OF LIFE WAYANG WONG SRIWEDARI PLAYERS - Gilang Rastu Gati; Zaenal Abidin (Faculty of Psychology, Diponegoro University, 2014)
The meaning of life is something that is considered important, valuable, and desirable as well as provide special value to one's self. The meaning of life is also worthy life goals. This study aims to find a vision of the meaning of life from the players who are in the wayang wong Sriwedari in Surakarta. This study used a qualitative method using a phenomenological approach. The number of subjects in the study were four people determined purposively. The results obtained from this study is the background in the selection of the fourth subject wayang wong job as a player because it has the talent and have ancestors who are involved in the arts wayang wong. Reason subjects persist in work because they love their work, do not have any other skills, and the desire to work. They also have the same goal in the work is provide for his family. Fourth research subject grateful for what they have earned, and considers his life prosperous. Physical changes to give effect to the subject in the work, other than that obtained in any role the show has been changed into buto figures and waistband. Achievement of the meaning of life is obtained subject of happiness, work wholeheartedly, loving family, successful children, produce works of art, to support my wife and kids, and the third male subjects have in common is their role as a father. Their efforts in achieving the meaning of life is done through the value of work, and the value being the value appreciation.